2003
DOI: 10.1038/sj.bjp.0705145
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of P2 purinergic receptors induces the release of eosinophil cationic protein and interleukin‐8 from human eosinophils

Abstract: 1 Extracellular nucleotides are the focus of increasing attention for their role as extracellular mediators since they are released into the extracellular environment in a regulated manner and/or as a consequence of cell damage. 2 Here, we show that human eosinophils stimulated with different nucleotides release eosinophil cationic protein (ECP) and the chemokine interleukin 8 (IL-8), and that release of these two proteins has a different nucleotide requirement. 3 Release of ECP was triggered in a dose-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 47 publications
2
63
1
1
Order By: Relevance
“…UDP alone has been shown to induce IL-8 release in the THP-1 monocytic cell line and human mature dendritic cells, 27,28 whereas ATP and UDP stimulate human eosinophils to produce IL-8. 26 In light of the direct stimulatory role of nucleotides to selectively induce IL-8 in different cell types 26,27 and the similar effects of HNPs and nucleotides, we demonstrated that the use of the P2 receptor antagonists suramin and reactive blue almost completely blocked HNP-induced IL-8 production. However, there appeared to be no direct interaction between HNP and P2 receptors because ATP and UDP did not compete with HNPs on cell-surface binding, or at least HNPs did not appear to share the same binding sites with ATP and UDP.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…UDP alone has been shown to induce IL-8 release in the THP-1 monocytic cell line and human mature dendritic cells, 27,28 whereas ATP and UDP stimulate human eosinophils to produce IL-8. 26 In light of the direct stimulatory role of nucleotides to selectively induce IL-8 in different cell types 26,27 and the similar effects of HNPs and nucleotides, we demonstrated that the use of the P2 receptor antagonists suramin and reactive blue almost completely blocked HNP-induced IL-8 production. However, there appeared to be no direct interaction between HNP and P2 receptors because ATP and UDP did not compete with HNPs on cell-surface binding, or at least HNPs did not appear to share the same binding sites with ATP and UDP.…”
Section: Discussionmentioning
confidence: 83%
“…on March 28, 2019. by guest www.bloodjournal.org From pathways including P2Y 2 (ATP ϭ UTP) and P2Y 4 (UTP ϾϾ ATP) receptors, P2X ligand-gated ion channels, 26 and adenosine resulting from ATP degradation by nucleotidases through A 2b receptor 30,31 (Figure 1). Involvement of these pathways was investigated with the use of specific blockers.…”
Section: Atp-dependent Signaling Plays a Minor Role In Hnp-induced Ilmentioning
confidence: 99%
See 1 more Smart Citation
“…MuLV Reverse Transcriptase (Applied Biosystems, Foster City, CA) was used to synthesize first-strand cDNA with oligo-dT [16][17][18] primer (Invitrogen, Carlsbad, CA) from 1 µg of the purified total RNA at 42°C for 60 min. A pair of the sequence-specific primers with Xho I sites were designed based on the published human P2X 7 cDNA sequence to amplify the entire coding sequence of the human P2X 7 subunit by PCR [53].…”
Section: Methodsmentioning
confidence: 99%
“…P2X 7 receptors are predominantly expressed on cells from the hematopoietic lineages, such as erythrocytes, lymphocytes, neutrophils, eosinophils, mast cells, monocytes, and macrophages [9][10][11][12][13][14][15][16][17][18]. It has been reported recently that P2X 7 receptors are expressed in central and spinal cord neurons [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%